2022
DOI: 10.1002/andp.202200304
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Optics Parity Effect on Generalized NOON States and Its Implications for Quantum Metrology

Abstract: NOON states are entangled states of great interest in the development of quantum technologies, because they enable high‐precision phase measurements in interferometric schemes relevant to quantum metrology and sensing. This study shows that two degenerate modes of a cavity field coupled to an atom or molecule that can be modeled as a two‐level system through two‐photon interactions, initially prepared in a (generalized) NOON state, experience a dynamical evolution that distinctly depends on the parity of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…The protocol does not work when N is even. Dependence on the parity of the total number of particles, in the study of time evolution of systems involving NOON states, has also been observed in[36].…”
mentioning
confidence: 88%
“…The protocol does not work when N is even. Dependence on the parity of the total number of particles, in the study of time evolution of systems involving NOON states, has also been observed in[36].…”
mentioning
confidence: 88%